A review of balancing methods for satellite simulators. (October 2021) - da Silva, Rodrigo Cardoso; Borges, Renato Alves; Battistini, Simone; Cappelletti, Chantal
Abstract: This article presents a general review of the existing methods for balancing satellite simulators. The mathematical modeling for the kinematics and the dynamics of the satellite simulator is described and uniformed throughout the various methods. The available balancing methods are classified in a handful group of categories, which consider whether the analyzed method uses linear or nonlinear filtering, adaptive control or even classical regression methods. Details are given on the features which may be added to the dynamic model and how they are modeled, on the discretization methods used, on the models observability and on the solution convergence. Finally, the overall performance of each method is shown, as well as the circumstances in which each method presents advantages and disadvantages, guiding on which method to use. Highlights: A general review of the existing methods for balancing satellite simulators. Guide on decreasing the gravitational torque disturbance in the simulator. Comparison between balancing methods and possible improvements. Methodology for assessing the performance of a given balancing method.